Răspuns :
Notez (x+3)=a si (x-4)=b.
[tex](x+3) ^{2} +2(x-4)(x+3)+(x-4)^{2} = a^{2} +2ab+b ^{2} =(a+b) ^{2}= \\ =[(x+3)+(x-4)]^{2}=(2x-1)^{2} [/tex]
[tex](x+3) ^{2} +2(x-4)(x+3)+(x-4)^{2} = a^{2} +2ab+b ^{2} =(a+b) ^{2}= \\ =[(x+3)+(x-4)]^{2}=(2x-1)^{2} [/tex]
[tex](x+3) ^{2} +2(x-4)(x+3)+(x-4) ^{2} = \\ =x^{2} +6x+9+2( x^{2} +3x-4x-12)+ x^{2}-8x+16= \\ = x^{2} +6x+9+2( x^{2} -x-12)+ x^{2} -8x+16= \\ = x^{2} +6x+9+2 x^{2} -2x-24+ x^{2} -8x+16= \\ =4 x^{2} -4x+1= 2^{2} x^{2} -4x+1=(2x-1)^{2} [/tex]